FEATURES AND PERSPECTIVES OF THE DEVELOPMENT OF ELECTRONIC COMMERCE - E. Bratischeva; I. Chepurova; A. Gladysheva (Вестник Северо-Кавказского федерального университета)
The global network for people is not only a number of cognitive possibilities, but also communication between users. This is completely new level because the Internet is an integral part of business in modern times. We can see that all new online stores, unique products and services offered by various users on the Internet open new opportunities, new approaches and new e-commerce solutions. We evaluate access to information technology and the network in the article. We examined the current problems of e-commerce and suggested solutions, revealed the features and main trends of the market. E-commerce occupies a large market share.